Revealing the impact of loss: Exploring mental health through the use of drawing/writing with HIV positive adolescents in Johannesburg. (June 2017) - Woollett, Nataly; Brahmbhatt, Heena; Dodd, Kate; Booth, Michelle; Berman, Hayley; Cluver, Lucie
Highlights: Loss and bereavement are pervasive in the lives of perinatally infected HIV positive adolescents. Drawings and writing highlight contextual deprivation, including high exposure to multiple losses of significant attachment figures. They also underscore emotional impoverishment, including unresolved complicated grieving impacting on mental health functioning. Innovative methods are required to address unmet mental health needs of this patient population. Using non-verbal methods by healthcare professionals could be valuable to both patient and provider, particularly when managing bereavement.